The life experience of leprosy families in maintaining interaction patterns in the family to support healing in leprosy patients in Indonesian society. A phenomenological qualitative study. - Abd Nasir; Ah Yusuf; Muhammad Yulianto Listiawan; Makhfudli Makhfudli (Public Library of Science (PLoS), 2022)
Background Family involvement in overcoming the severity of leprosy is very important in the life of leprosy sufferers in communities who experience the clinical and, psychological, social and behavioral consequences of the disease. However, this need, psychosocial, is felt to be not optimal. This study is to identify how the experiences of family members as caregivers provide assistance to individuals with leprosy in improving healing and maintaining patterns of interaction in the family. Methods The design uses qualitative research with in-depth, face-to-face interviews with family members in a semi-structured manner with the hope of obtaining complete data. Using purposive sampling with Participatory Interpretative Phenomenology analysis, there are 12 families with 15 family members consisting of 4 men and 11 women. Results This study produced a family theme that tried to follow what would happen to individuals with leprosy, with four sub-categories: 1) Using various coping alternatives to recognize the disease, 2) Family members in the shadow of leprosy, 3) Trying to empathize with other family members. sick, 4) Caring for the emotional response of the family and seeking support. Conclusions This analysis shows that deficiency in cognitive aspects can be closed by maintaining a lifestyle in the family through efforts to understand, support, establish communication, increase maximum involvement in restoring self-confidence, especially in individuals with leprosy with psychosocial problems in the family. The results of this study can be used as psychosocial support in maintaining communication between family members to support treatment programs and accelerate the recovery of leprosy.